Evaluation of adolescents' status of the first-step health services use and healthy nutrition behaviors - Tetik, Burcu Kayhan; Tekinemre, Isilay Gedik; Kurt, Osman (Eurasian Society of Family Medicine, 2021)
Aim: This study aimed to evaluate the status of the first-step health services use, healthy nutrition behaviors in adolescents and investigate their relationships with each other. Methods: One hundred and forty-six adolescents between the ages of 10 and 18 were included in this descriptive study. A survey of 15 questions about the participants' healthy nutritional behaviors, the status of knowing their family physicians, and going to their family physicians for the examination was applied. The obtained data were analyzed using the SPSS 22 package program, and p <0.05 was considered significant. Results: Of the participants, 85.6% went to their family physicians for the examination, the mean age was 16.4±1.6, and 58.9% were girls. Girls' mean scores of healthy nutritional behavior and going to their family physicians for the examination were significantly higher than boys'. In those who were obese and overweight, the rate of knowing their family physicians, the mean score of going to their family physicians for the examination, and healthy nutritional behavior were lower than normal weight. Conclusion: In our study, lower obesity and overweight rates and having a healthier diet were seen in adolescents using primary health care services more. We believe that to eliminate obesity, which has been a significant public health problem today, increasing the rate of using primary health care services for adolescent individuals needs to be increased. We hope that our comments raised herein will encourage other physicians to be more sensitive about this issue and direct patients to primary care more often to receive such services. © 2021, Eurasian Society of Family Medicine. All rights reserved.
Keywords: Adolescents; Nutrition behavior; Primary health care